BS25 TAM receptor AXL loss regulates smooth muscle cell differentiation and accelerates atherosclerosis in mice. (4th June 2021) - Mcshane, Lucy; Gurgone, Danila; Bin-Khunayn, Abdullatif Mohammed; Crespo, Eva; Grassia, Gianluca; MacRitchie, Neil; Giacca, Mauro; Zentilin, Lorena; Karadimou, Glykeria; Paulsson-Berne, Gabrielle; Olofsson, Peder S; Otto, Thomas D; et al.
Abstract : Introduction: The TAM receptors (Tyro3, Axl, and MerTK) are a distinct family of three receptor tyrosine kinases, namely Tyro3, Axl and MerTK, which play critical roles in cancer, inflammatory disorders and cardiovascular diseases. Axl, in particular, has been shown to influence multiple aspects of cardiovascular pathology via diverse effects on cells of both the vasculature and immune system through regulation of vascular remodelling, efferocytosis and inflammation. Clinical studies have shown that Axl is detectable in atherosclerotic plaques; however, the causal relationship between Axl and atherosclerosis is still uncertain, and results from mouse models fell short of defining the specific role(s) of Axl in the disease process. Methods: In order to quantify Axl expression in carotid endarterectomy atherosclerotic plaques we examined data from the Biobank of Karolinska Endarterectomy (BiKE). Using single-cell RNA sequencing (scRNA-seq) data from published atherosclerosis datasets we determined which cell types express Axl during pathology. Finally, we utilised an inducible atherosclerosis model in order to assess atherosclerosis formation in global Axl-deficient mice (Axl-/-). Female C57BL/6NQ (WT; n=15) and Axl-/- (n=21) mice were injected with 3×1011 vector genomes of AAV8-proprotein convertase subtilisin/kexin type 9 (PCSK9) and placed on a Western Diet (WD) for 12 weeks. Plaque size and percentage of necrotic core were determined in the aortic sinus using Oil Red O (ORO). Collagen content was determined using picrosirius red and polarised light microscopy. ScRNA-seq was performed to explore differences in Axl-/- vs. WT aortas at the cellular and molecular level. Results: We found expression of Axl in human carotid plaque to be significantly reduced in comparison to healthy control tissue (P=1.96e-06) in the BiKE cohort. Similarly, we detected less Axl RNA expression in the aortas of WD-fed apolipoprotein-E-/- mice compared to WT (P<0.05). Analysis of published scRNA-seq databases found that Axl is expressed predominantly in the vascular smooth muscle cell (VSMC) compartment of the aortas in both healthy and atherosclerotic mice, with expression also observed in fibroblasts and macrophages. Global Axl-deficiency increased lesion size in the aortic sinus (P<0.001). While collagen content and necrotic core were not affected. ScRNA-seq on the aortas showed a switch versus a less contractile smooth muscle cell phenotype in Axl-/- mice compared to WT. Conclusions: In conclusion, our results indicate a protective role for Axl in atherosclerosis. The TAM receptor is reduced in diseased vessel compared to healthy controls in both human and mouse. Furthermore, global knock-out resulted in significantly increased plaque burden in mice. The necrotic core was not found to be influenced by Axl, suggesting that TAM receptor-mediated efferocytosis is not a key contributor to the role of Axl in atherosclerosis. Axl was found to be predominantly expressed in the VSMC compartment in the aortas of both healthy and diseased mice. Furthermore, Axl deficiency promoted VSMC phenotypic switching. These data support the hypothesis of a beneficial role of Axl in atherosclerosis via modulation of smooth muscle cell phenotype. Conflict of Interest: none